2016
DOI: 10.1164/rccm.201604-0753oc
|View full text |Cite
|
Sign up to set email alerts
|

A Distinct Low Lung Function Trajectory from Childhood to the Fourth Decade of Life

Abstract: A distinct group of individuals in a nonselected population demonstrates a persistently low lung function trajectory that may be partly established at birth and predisposes them to chronic obstructive pulmonary disease later in life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
159
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(166 citation statements)
references
References 28 publications
5
159
1
1
Order By: Relevance
“…Many studies have suggested that children with an episode of RSV-related bronchiolitis in infancy are more likely to have recurrent wheeze [3,16], especially if their bronchiolitis was severe [17]. Followed up over time, these children have spirometric values consistent with reduced airway patency at school age [4,16,18]. A similar association has been found for HRV-related bronchiolitis, too [19].…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Many studies have suggested that children with an episode of RSV-related bronchiolitis in infancy are more likely to have recurrent wheeze [3,16], especially if their bronchiolitis was severe [17]. Followed up over time, these children have spirometric values consistent with reduced airway patency at school age [4,16,18]. A similar association has been found for HRV-related bronchiolitis, too [19].…”
Section: Discussionmentioning
confidence: 60%
“…Recently, a birth cohort study that has been ongoing for almost 4 decades showed that respiratory syncytial virus (RSV) infection of the lower respiratory tract during early life is associated with a persistently low trajectory of lung function that represents an important pathway to chronic obstructive pulmonary disease [4].…”
mentioning
confidence: 99%
“…13 In further follow up, 599 subjects showed a stable, low lung function trajectory from age 11 to 32, with spirometry taken every 4–6 years. 14 These studies demonstrate that when low lung function accompanies childhood asthma, that low lung function tends to persist into adulthood.…”
Section: Childhood Cohortsmentioning
confidence: 85%
“…Most asthmatics start wheezing in early childhood . Patients with COPD may have early life symptoms and airflow obstruction, and there are associations between COPD‐associated genes and transient early symptoms of wheeze …”
Section: Introductionmentioning
confidence: 99%
“…4 Most asthmatics start wheezing in early childhood. 5,6 Patients with COPD may have early life symptoms and airflow obstruction, 7,8 and there are associations between COPD-associated genes and transient early symptoms of wheeze. 8 Currently, it is difficult to predict if early childhood wheeze will remit or is the precursor of persistent wheezing/asthma.…”
Section: Introductionmentioning
confidence: 99%